iTRAQ-based proteomic analysis reveals the mechanisms of Botrytis cinerea controlled with Wuyiencin - Liming Shi; Beibei Ge; Jinzi Wang; Binghua Liu; Jinjin Ma; Qiuhe Wei; Kecheng Zhang (BMC Microbiology, 2019)
Abstract Background Grey mould is an important plant disease worldwide, caused by Botrytis cinerea, resulting in serious economic loss. Wuyiencin, a low toxicity, high efficiency, and broad-spectrum agricultural antibiotic, has been demonstrated effectiveness against B. cinerea. Results Wuyiencin treatment inhibited growth and sporulation of B. cinerea, specifically altering hypha morphology and intracellular structures. These changes were accompanied by differential expression (fold change > 2.0) of 316 proteins identified by iTRAQ-labelling LC-MS/MS analysis (P < 0.05). Up-regulation of 14 proteins, including carbohydrate metabolism proteins and cell wall stabilization proteins, was validated by parallel reaction monitoring (PRM). Down-regulation of 13 proteins was validated by PRM, including regulators of energy metabolism, nucleotide/protein synthesis, and the biosynthesis of mediators of plant stress and decay. Conclusion Our results confirm the inhibitory biological effects of wuyiencin on B. cinereal and elaborate on the differentially expressed proteins and associated pathways implicated in the capacity of wuyiencin to debilitate the growth and pathogenicity of grey mould. This study provides validated candidates for further targeted exploration with the goal of optimizing wuyiencin as a safe, low-toxicity agent for biological control.